2012
DOI: 10.1016/j.atmosenv.2011.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Springtime Arctic aerosol: Smoke versus haze, a case study for March 2008

Abstract: a b s t r a c tDuring March 2008 photometer observations of Arctic aerosol were performed both at a Russian ice-floe drifting station (NP-35) at the central Arctic ocean (56.7e42.0 E, 85.5e84.2 N) and at Ny-Ålesund, Spitsbergen (78.9 N, 11.9 E). Next to a persistent increase of AOD over NP-35, two pronounced aerosol events have been recorded there, one originating from early season forest fires close to the city of Khabarovsk ("Arctic Smoke"), the other one showed trajectories from central Russia and resembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
3
19
1
1
Order By: Relevance
“…However, Stock et al (2011) have already reported higher AOD values over the more remote Russian drifting station NP-35 than over Ny-Å lesund. Moreover, Toledano et al (2012) gave an overview of sun photometer measurements at different Arctic sites.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, Stock et al (2011) have already reported higher AOD values over the more remote Russian drifting station NP-35 than over Ny-Å lesund. Moreover, Toledano et al (2012) gave an overview of sun photometer measurements at different Arctic sites.…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, our knowledge of precise microphysical properties of Arctic aerosols (size distribution, shape, index of refraction) is still limited. While the phenomenon of Arctic haze for accumulation mode particles mainly consisting of sulphates and soot has been known for many years (Shaw, 1995;Quinn et al, 2007), recently biomass burning was also found to be one of the important sources of Arctic air pollution (Warneke et al, 2009;Stock et al, 2011) even in early spring. *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Lidars also provide an indication of particle size from spectral channels and particle shape via the depolarization channels. The combined use of sunphotometers and lidar, accompanied by supplementary backward trajectories, satellite and other data, has been successfully applied to characterize Arctic aerosol events during the summer time (see, e.g., O'Neill et al, 2008a;Hoffmann et al, 2010;Stock et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Special concern is directed on biomass and diesel combustion sources which degrade the Arctic air quality by depositing BC on snow and melting icecaps (Matsui et al, 2011). Seasonal BB activities in Siberia may double the climate-relevant species, including BC and organic aerosols (Warneke et al, 2010), and cause the pronounced pollution event of "Arctic smoke" (Stock et al, 2012). Despite the concerns about environmental significance of millions of tons of PM emitted by wildfires, systematic observations in Russia were performed only in a few places in Western and North-Eastern Siberia (Kozlov et al, 2008;Paris et al, 2009).…”
Section: Introductionmentioning
confidence: 99%